FROM HUMAN CAPITAL TO MARGINALIZED OTHER: A SYSTEMATIC REVIEW OF DIASPORA AND INTERNATIONALIZATION IN HIGHER EDUCATION. Issue 3 (4th May 2022) - Bamberger, Annette
ABSTRACT: The proliferation of diasporas has influenced the nature of internationalization in many higher education (HE) systems and institutions, especially in terms of academic and student mobility/migration. Through a systematic review of the academic literature, I critically analyze the widespread uses of and approaches to 'diaspora' in HE research and its relationship to internationalization. I identify two major areas of studies and corresponding approaches to diaspora: one which frames diaspora as human capital and focusses on the role of the state; and the other which frames diaspora as marginalized other and social construct. I argue that 'diaspora' in HE studies tends to be ambiguous, under-defined, under-theorized, and fragmented. I further argue that it is loosely connected to internationalization discourses, despite its clear connections. I posit that this is because 'internationalization' is associated with humanitarianism, cosmopolitanism, global citizenship and the de-centering of states, nations, ethnicities, religions, and particularistic identities. Diaspora is often associated with these latter categories and thus, is shunned. I conclude by suggesting that the blending of (often conflictual) ideas, intentions, values and identities is precisely what diaspora engages in and that the conditions of our increasingly mobile and (inter)connected world necessitate a (re)thinking of diaspora in HE scholarship.